Laser-induced and space-selective crystallization of yttrium aluminum garnet crystal from SiO2/Al2O3/Y2O3/KF/Na2O/AlF3/B2O3 glass system. Issue 5 (6th January 2021) - Doosti, Azadeh; Keshavarzi, Ashkan; Safari Yazd, Nazila; Leriche, Anne
Abstract : Femtosecond laser-induced crystallization in glasses is of interest because of its significant applications in optics and photonics. Abstract : Femtosecond laser-induced crystallization in glasses is of interest because of its significant applications in optics and photonics. Micro-YAG crystals produced by controlled crystallization from a glassy matrix is one of the studied material to achieve this goal. In this work, a three-dimensional (3D) space-selective crystallization of YAG by femtosecond laser irradiation was investigated in yttrium aluminosilicate glass. Independent cubic YAG crystals of a tenth μm edge were grown in a glass sample depth for 20, 30 and 40 seconds irradiation. The crystallization mechanism was discussed in both static and dynamic mode by illustrating the distribution of different gradients. The YAG crystals grew on the surface and at various depths of the glass matrix with particular morphologies depending on the laser application mode.